4D printing of electroactive shape-changing composite structures and their programmable behaviors. (June 2022) - Dong, Xinyu; Zhang, Fenghua; Wang, Linlin; Liu, Yanju; Leng, Jinsong
Abstract: 4D printing is an advanced manufacturing technology that combines the convenience of additive manufacturing and uses stimuli-responsive materials, which has great application potentials in the field of smart structures. Using electroactive shape memory polymer composites (SMPCs), smart devices with remote control capabilities without a heat source can be prepared by 4D printing. In this work, a variety of 4D printed structures based on PLA/CNT composites were fabricated by FDM. Electroactive SMPC filaments with different CNT contents were prepared, and their electrical, thermal, and shape-memory properties were investigated. Moreover, a series of 2D and 3D printed complex structures were designed and manufactured to realize their shape recovery behavior under the electrical field. The relationship between the electroactive shape-memory performance of 4D printed structures, structural design, and printing parameters was obtained. This work could provide a new feasible way for the design and manufacturing of electroactive devices in the future.